2022
DOI: 10.1097/cm9.0000000000002277
|View full text |Cite
|
Sign up to set email alerts
|

Estimating global prevalence, incidence, and outcomes of non-alcoholic fatty liver disease from 2000 to 2021: systematic review and meta-analysis

Abstract: Background: The increasing burden of non-alcoholic fatty liver disease (NAFLD) worldwide imposes an emerging public health issue. We perform the current study to estimate the global prevalence, incidence, disease progression, and clinical outcomes of NAFLD. Methods: A systematic search was conducted in Medline, Embase, Web of Science, Google Scholar, and Cochrane CENTRAL that screened articles in English language published from January 2000 to December 2021. NAFLD preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Studies were not excluded based on their quality score in order to promote transparency and guarantee that all pertinent evidence in this area was provided. The "Metaprop" module in the R-4.0.2 statistical software package was used for meta-analysis after ensuring consistency (13)(14)(15)(16)(17). A 95% confidence interval (95% CI) was generated using Wilson score method, and the DerSimonian-Laird random effects model with Logit transformation was used to compute the pooled prevalence.…”
Section: Quality Assessment and Statistics Analysismentioning
confidence: 99%
“…Studies were not excluded based on their quality score in order to promote transparency and guarantee that all pertinent evidence in this area was provided. The "Metaprop" module in the R-4.0.2 statistical software package was used for meta-analysis after ensuring consistency (13)(14)(15)(16)(17). A 95% confidence interval (95% CI) was generated using Wilson score method, and the DerSimonian-Laird random effects model with Logit transformation was used to compute the pooled prevalence.…”
Section: Quality Assessment and Statistics Analysismentioning
confidence: 99%
“…Studies have reported MASLD prevalence rates of 76% and 93% in obese individuals, with progression rates to MASH of 37% and 26%, respectively. [46][47][48] The annual incidence of HCC in MASLD patients is 1.3 cases per 1000 person-years, which suggests a recent increase compared to previous published estimates. 9 In some cases, MASLD-related HCC may develop without a cirrhosis background, making it difficult to estimate the exact HCC incidence in MASLD patients.…”
Section: Accepted Manuscriptmentioning
confidence: 74%
“…NAFLD is the most common chronic liver disease, encompassing a spectrum of liver injuries ranging from fatty liver disease to liver cirrhosis ( Setiawan et al, 2016 ; Younossi et al, 2018 ). The prevalence of NAFLD has been increasing (25.24% in 2015 to 29.38% in 2021) ( Younossi et al, 2016 ; Liu et al, 2022 ), accounting for 45.8% of the total causes of death from chronic liver disease ( Golabi et al, 2022 ). Non-alcoholic steatohepatitis (NASH) refers to an advanced form of NAFLD, and it is characterized by the presence of hepatic steatosis with hepatocellular injury (hepatocyte ballooning) and inflammation, which is one of the main causes of cirrhosis and hepatocellular carcinoma ( Goldberg et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%